PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING PADA PEMBELAJARAN MATEMATIKA - M. Jainuri; Ade Susanti; Fuspela Prindiyati (Mat-Edukasia, 2021)
This study aims to produce LKPD based on discovery learning that is valid, practical and effective. This research is research and development (R&D). The LKPD developed was validated by five validators, namely three material expert validators, one linguist validator and one media expert validator. The average result of material expert validation is 4,67, linguistic expert validation is 4,50, media expert validation is 5,00 and math teacher validation is 4,77 with the results of the overall validation category being very valid. The percentage of the practicality questionnaire obtained was 73,25% with the practical category. While the percentage of student learning outcomes obtained by 84,21% with the effective category and the average percentage of student activity obtained 61,99% with the active category. Based on the results of research and development, it shows that the LKPD based on discovery learnin developed are valid, practical and effective.